Relative Measurement Errors in Valuing Plant and Equipment under Current Cost and Replacement Cost - Swanson, Edward P. (The Accounting Review, 1990)
[Measurement errors may have reduced the usefulness of current-cost and replacement-cost data. Under the provisions of Accounting Series Release No. 190 (ASR 190), replacement-cost valuations of plant and equipment (and related depreciation) often include the cost of technological advances and often these advances would reduce operating costs below the level reported by historical cost. As a result, when replacement-cost depreciation is substituted for historical-cost depreciation, the cost of doing business includes the high capital cost of the advanced technology as well as the high operating costs of the older technology in use, which creates measurement errors. ASR 190 was criticized because the reported depreciation amounts are not suitable for calculating income. Although Statement of Financial Accounting Standards No. 33 (FAS 33) includes provisions to remedy this problem, they may not have been effective because relatively few firms have reduced related depreciation expense to adjust for the present value of operating-cost savings. Moreover, numerous firms have relied on price indexes, which are not known to fully reflect technological changes. Therefore, the question arises as to whether current-cost data have substantially less measurement errors than replacement cost-data as a result of ignoring the effects of technological change. Analysis of a sample of 75 firms that reported under both methods for 1979 shows that current-cost depreciation is substantially smaller than replacement-cost depreciation for most firms. This finding suggests the presence of a smaller measurement error from technological change in the current-cost data compared with replacement-cost data. Nevertheless, additional analyses indicate the existence of measurement error in current-cost data also. First, an error component is common to about 25 percent of the sample firms that reported almost identical depreciation amounts under current cost and replacement cost. Second, the excess of replacement-cost depreciation over current-cost depreciation is not in proportion with the amount of potential operating-cost savings described in narrative disclosures accompanying the replacement-cost data. If these narrative disclosures are accurate, this divergence suggests incomplete adjustments of current-cost data for this type of technological change. Third, potential tax incentives may have influenced the measurement of current cost. Voluntary disclosure of effective tax rates on a current-cost basis is associated with the choice of measurement method (greater use of indexation). Moreover, current-cost and replacement-cost depreciation are relatively more similar for firms disclosing effective tax rates than for nondisclosing firms (suggesting smaller adjustments for technological change in current-cost data, which results in higher current-cost tax rates).]